Septin‐5 and ‐7‐IgGs: Neurologic, Serologic, and Pathophysiologic Characteristics. Issue 6 (27th August 2022) - Hinson, Shannon R.; Honorat, Josephe A.; Grund, Ethan M.; Clarkson, Benjamin D.; Miske, Ramona; Scharf, Madeleine; Zivelonghi, Cecilia; Al‐Lozi, Muhammad Taher; Bucelli, Robert C.; Budhram, Adrian; Cho, Tracey; Choi, Ellie; et al.
Abstract : Background and Objectives: We sought to determine clinical significance of neuronal septin autoimmunity and evaluate for potential IgG effects. Methods: Septin‐IgGs were detected by indirect immunofluorescence assays (IFAs; mouse tissue and cell based) or Western blot. IgG binding to (and internalization of) extracellular septin epitopes were evaluated for by live rat hippocampal neuron assay. The impact of purified patient IgGs on murine cortical neuron function was determined by recording extracellular field potentials in a multielectrode array platform. Results: Septin‐IgGs were identified in 23 patients. All 8 patients with septin‐5‐IgG detected had cerebellar ataxia, and 7 had prominent eye movement disorders. One of 2 patients with co‐existing septin‐7‐IgG had additional psychiatric phenotype (apathy, emotional blunting, and poor insight). Fifteen patients had septin‐7 autoimmunity, without septin‐5‐IgG detected. Disorders included encephalopathy (11; 2 patients with accompanying myelopathy, and 2 were relapsing), myelopathy (3), and episodic ataxia (1). Psychiatric symptoms (≥1 of agitation, apathy, catatonia, disorganized thinking, and paranoia) were prominent in 6 of 11 patients with encephalopathic symptoms. Eight of 10 patients with data available (from 23 total) improved after immunotherapy, and a further 2 patients improved spontaneously. Staining of plasma membranes of live hippocampal neurons produced by patient IgGs (subclasses 1 and 2) colocalized with pre‐ and post‐synaptic markers. Decreased spiking and bursting behavior in mixed cultures of murine glutamatergic and GABAergic cortical neurons produced by patient IgGs were attributable to neither antigenic crosslinking and internalization nor complement activation. Interpretation: Septin‐IgGs are predictive of distinct treatment‐responsive autoimmune central nervous system (CNS) disorders. Live neuron binding and induced electrophysiologic effects by patient IgGs may support septin‐specific pathophysiology. ANN NEUROL 2022;92:1090–1101